Advancing Women's Political Rights in Africa: The Promise and Potential of ACDEG. Issue 2 (August 2019) - Abdulmelik, Nebila; Belay, Tsion
This paper places women at the centre of analysis, examining the potential and promise of the African Charter on Democracy, Elections and Governance (ACDEG) in the advancement of women's political rights. This is a highly under-researched topic, necessitating a mapping of the current political landscape for women and an understanding of how ACDEG addresses these challenges as well as provides opportunities for advancing women's political participation. This paper argues that ACDEG provides a good basis and framework to operate from for member states – some of whom already have suitable policies, and more importantly suitable practices, in place that emerge from a range of normative frameworks, including the Maputo Protocol. ACDEG complements these frameworks and makes a further case for women's full and meaningful participation in public and private life by obligating states to take concrete steps to guarantee women's political rights. Considering this, the paper identifies prospects for women's rights activists and organisations to invoke ACDEG and monitor its implementation in the move towards the realisation of African women's political rights.